Optimizing Digital Marketing and Implementing Endorsements to Increase the Pineapple Chips Business Capacity - Sabda Dian Nurani Siahaan; Lenti Susanna Saragih; Siti Ulgari; Haryani Pratiwi Sitompul (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Entrepreneurship sector plays an important role in the nation progress. The partner in this Community Service is Maju Tani Group in Pakpak Bharat Regency. The purpose of this activity is to improve the pineapple chips business of the Maju Tani group in order to maintain business continuity. The problem found is the product less recognized by the community. The solution offered to overcome this problem is to conduct digital marketing training and endorsement of pineapple chips on social media. The method of implementing this activity is training and mentoring. In this service activity, the service team helped partners create business social media and make a video endorsement of chips. All of this aims to increase the business capacity of partners. Overall, the service activities went smoothly.The Entrepreneurship sector plays an important role in the nation progress. The partner in this Community Service is Maju Tani Group in Pakpak Bharat Regency. The purpose of this activity is to improve the pineapple chips business of the Maju Tani group in order to maintain business continuity. The problem found is the product less recognized by the community. The solution offered to overcome this problem is to conduct digital marketing training and endorsement of pineapple chips on social media. The method of implementing this activity is training and mentoring. In this service activity, the service team helped partners create business social media and make a video endorsement of chips. All of this aims to increase the business capacity of partners. Overall, the service activities went smoothly.